2021
DOI: 10.1177/0361198121995500
|View full text |Cite
|
Sign up to set email alerts
|

Mining Vehicle Trajectories to Discover Individual Significant Places: Case Study using Floating Car Data in the Paris Region

Abstract: In this study we discovered significant places in individual mobility by exploring vehicle trajectories from floating car data. The objective was to detect the geo-locations of significant places and further identify their functional types. Vehicle trajectories were first segmented into meaningful trips to recover corresponding stay points. A customized density-based clustering approach was implemented to cluster stay points into places and determine the significant ones for each individual vehicle. Next, a tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…They were presegmented into trips and labeled with travel modes by the data provider. Relevant methods can be found in the existing literature ( 16 , 17 ) and ( 24 ). For carpooling-related purposes, only the vehicle-related trajectories were used in the following analysis.…”
Section: Application and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were presegmented into trips and labeled with travel modes by the data provider. Relevant methods can be found in the existing literature ( 16 , 17 ) and ( 24 ). For carpooling-related purposes, only the vehicle-related trajectories were used in the following analysis.…”
Section: Application and Resultsmentioning
confidence: 99%
“…A typical example could be an entity staying within a radius of 150 m for over 20 min. More details of such processing methods and relevant reviews of existing work can be found in our previous studies ( 16 , 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…As the FCD trace the entire path information, after the segmentation, the O-D flow, their assignment paths, and the partial flow pertaining to the marked vehicles by the FCD can be easily recovered. More specifically, the segmentation processing was done by identifying activity stops ( 30 ), whose patterns can be featured as staying at a place over a certain time threshold. To identify the path, a map-matching approach ( 31 ) was then employed to match the trajectory to the road network.…”
Section: Application Methodologymentioning
confidence: 99%
“…[16] built a mobility-related typology of territorial zones by investigating vehicle movements by FCD in the Great Paris region; they found that the derived mobility types of zones have a correspondence with the common recognition of their social functions. In addition, in [17], significant places have been localized in the Metropolitan Region of Paris by mining trajectories and activity durations from FCD.…”
Section: Introductionmentioning
confidence: 99%